Meningkatkan Hasil Belajar Siswa Melalui Penerapan Aplikasi Sway pada Mata Pelajaran Produksi Olahan Diversifikasi Hasil Perikanan - Siti Munawaroh (Universitas Tadulako, 2021)
This study aims to improve student learning outcomes in processed production diversified fishery products subjects for class XI APHPi students of SMK Negeri 1 Sanden. This study has used a two-cycle class action research model. Each cycle consists of three meetings. The research subjects who had been involved were 10 class XI students of the APHPi expertise competency at SMK Negeri 1 Sanden, totaling 10 female students. The research was conducted from July to October 2020. The research phase included planning, implementing actions, observing, and reflecting. The instruments that have been used are in the form of observation sheets, questionnaires, and multiple choice test questions. The results of the study have shown an increase in student learning completeness from 60% in cycle 1 to 90% in cycle 2. The average test results were 78 in cycle 1 and 85 in cycle 2. The application of sway-based online learning can improve the ability to apply the basic principles and flow of the food processing process.